(untitled) (Journal of Education and Development, 2021)
The Virtual Education was born in 2002 from a joint project between the Center for Improvement, Experimentation and Pedagogical Research CPEIP and the Center for Education and Technology Links. CPEIP has developed a line of distance teacher training through the Internet running several courses since 2002, and Links during the last 15 years has dedicated its efforts to provide the access of teachers and students to educational opportunities associated with new technologies of Information and communication. Both institutions decided to combine their efforts and develop a joint project that integrates the CPEIP distance teacher training line, up to now aimed at curriculum updating, different strategies to support the appropriation of ICTs and their curricular integration.